Family Support and Herbal-Use Practices among Senior High School Students with Previous Herbal Use - Kristin Augusthin Natalia Dahoklory; Abdul Thalib (Innovative Approaches in Health Science Journal, 2026)
Background: Family practices may shape adolescents’ use of herbal products, but greater use does not necessarily indicate safe or evidence-based use. Objective: To examine the association between family support for herbal use and herbal-use practice scores among senior high school students with previous herbal-use experience in Ambon, Maluku. Methods: This cross-sectional study included 89 purposively selected students at SMA Negeri 12 Ambon in November 2025. Family support and herbal-use practices were assessed using separate eight-item, four-point Likert questionnaires (score range, 8–32). Internal consistency coefficients were 0.866 and 0.861, respectively. Because both score distributions were non-normal, the association was examined using Spearman’s rank correlation. Results: Family support was positively associated with the herbal-use practice score (Spearman’s rho = 0.794, p < 0.001). Because both constructs were measured by self-report in the same session and may contain related content, the magnitude of the coefficient requires cautious interpretation. Conclusion: Among students with previous herbal-use experience at one school in Ambon, higher family-support scores were associated with higher herbal-use practice scores. The cross-sectional, selected-sample design does not establish directionality or causality and does not show that reported use was safe or evidence-based.